Larazotide acetate in patients with coeliac disease undergoing a gluten challenge: a randomised placebo‐controlled study. Issue 2 (19th November 2012) - Kelly, C. P.; Green, P. H. R.; Murray, J. A.; DiMarino, A.; Colatrella, A.; Leffler, D. A.; Alexander, T.; Arsenescu, R.; Leon, F.; Jiang, J. G.; Arterburn, L. A.; Paterson, B. M.; et al.
Summary Background Coeliac disease, an autoimmune disorder triggered by gluten ingestion, is managed by a gluten‐free diet (GFD), which is difficult for many patients. Larazotide acetate is a first‐in‐class oral peptide that prevents tight junction opening, and may reduce gluten uptake and associated sequelae. Aim To evaluate the efficacy and tolerability of larazotide acetate during gluten challenge. Methods This exploratory, double‐blind, randomised, placebo‐controlled study included 184 patients maintaining a GFD before and during the study. After a GFD run‐in, patients were randomised to larazotide acetate (1, 4, or 8 mg three times daily) or placebo and received 2.7 grams of gluten daily for 6 weeks. Outcomes included an experimental biomarker of intestinal permeability, the lactulose‐to‐mannitol (LAMA) ratio and clinical symptoms assessed by Gastrointestinal Symptom Rating Scale (GSRS) and anti‐transglutaminase antibody levels. Results No significant differences in LAMA ratios were observed between larazotide acetate and placebo groups. Larazotide acetate 1‐mg limited gluten‐induced symptoms measured by GSRS (P = 0.002 vs. placebo). Mean ratio of anti‐tissue transglutaminase IgA levels over baseline was 19.0 in the placebo group compared with 5.78 (P = 0.010), 3.88 (P = 0.005) and 7.72 (P = 0.025) in the larazotide acetate 1‐, 4‐, and 8‐mg groups, respectively. Adverse event rates were similar between larazotide acetate and placebo groups. Conclusions Larazotide acetate reduced gluten‐induced immune reactivity and symptoms in patients with coeliac disease undergoing gluten challenge and was generally well tolerated; however, no significant difference in LAMA ratios between larazotide acetate and placebo was observed. Results and design of this exploratory study can inform the design of future studies of pharmacological interventions in patients with coeliac disease.